Mechanochemical Synthesis of Cu2MgSn3S8 and Ag2MgSn3S8. Issue 1 (3rd January 2020) - Heppke, Eva Maria; Klenner, Steffen; Janka, Oliver; Pöttgen, Rainer; Lerch, Martin
Abstract : Two new thiospinels of the type A I 2 B II C IV 3 S VI 8 were successfully synthesized via a mechanochemical route using binary sulfides and sulfur. Cu2 MgSn3 S8 and Ag2 MgSn3 S8 are the first A I 2 B II C IV 3 S VI 8 compounds with magnesium as divalent cation. The crystal structures of Cu2 MgSn3 S8 and Ag2 MgSn3 S8 were refined in the cubic space group Fd 3 m using X‐ray powder diffraction. According to UV/Vis measurements, a direct optical bandgap of ca. 1.65 eV was determined for both Cu2 MgSn3 S8 and Ag2 MgSn3 S8 . Temperature‐dependent magnetic susceptibility measurements of the Cu2 MgSn3 S8 sample indicate diamagnetism. A 119 Sn Mössbauer spectrum confirms the tetravalent state of tin, underlining the electron‐precise description. Abstract :